Dietary intake by food group of individuals with type 2 diabetes mellitus: A systematic review. (March 2018) - Burch, Emily; Ball, Lauren; Somerville, Mari; Williams, Lauren T.
Abstract: Aims: To synthesize peer-reviewed literature that investigates the dietary intake by food group of individuals with type 2 diabetes mellitus (T2DM) and compare intakes to national and international dietary guidelines. Methods: Four electronic databases (MEDLINE, EMBASE, CINAHL and Web of Sciences) were searched for studies that investigated the dietary intake of adults (≥18 years) with T2DM using the five main food groups (fruit, vegetables, dairy, grains and meat/meat alternatives). Food group intake in serves was compared against national guidelines and fruit and vegetable intake in grams was compared against the World Health Organization (WHO) guidelines. Results: After screening 13, 662 publications, 11 studies were included. All reported cross-sectional data. Majority of participants were consuming less than the recommended serves of fruit, vegetables, grains and dairy and were meeting or exceeding the recommended serves for meat/meat alternatives. Two of six studies reported fruit and vegetable recommendations were being met, two reported dairy recommendations were being met and two reported grain recommendations were being met. Of the five studies reporting intake in grams, four met the WHO minimum intake for fruit and vegetables. Conclusions: Individuals with T2DM do not comply with food group recommendations; particularly for fruit, vegetables, dairy and grains. Longitudinal research is required to better understand how food group intake changes over time after diagnosis.